Evaluasi Modal Sosial pada Sistem Agroforestri: Studi Kasus Desa Argosari, Malang - Rita Parmawati; Soemarno Soemarno; Agung Sih Kurnianto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Agroforestry activities are carried out in order to obtain community welfare, both in and around forests and at the same time also maintaining primary forest. Agroforestry can provide long-term benefits, such as increased crop productivity, more sustainable land use, as well as soil and environmental conservation. The success of forest management through agroforestry is determined by the level of community participation in forest management and the quality of human resources. The aim of the research was to identify and analyze several factors that strengthen social capital of agroforestry system in Argosari village and its sustainability. Using quantitative approach with Multi Dimensional Scaling (MDS)-Rap-agroforestry, all research variable (trust, ecology, social, and agroforestry) perceived as neutral by respondents. The Rap-agroforestry found that all dimensions studied are quite accurate and can be justified, where stress value ranges between 0.15-0.21 and coefficient of determination value is 0.910.97. The sustainability index is as follows: ecology (54.68), economy (36.46), and social (45.40). The difference between the sustainability index and Monte Carlo are so small : ecology (0.32), economy (0.86), and social (0.31), so that the sustainability index can be used to conduct a sustainability  assesment of the agroforestry system in Argosari village. This is very important for future policy formulation.